2020
DOI: 10.1016/j.geomorph.2019.106917
|View full text |Cite
|
Sign up to set email alerts
|

Chute cutoff-driven abandonment and sedimentation of meander bends along a fine-grained, non-vegetated, ephemeral river on the Bolivian Altiplano

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…The Río Colorado is characterised by seasonal activation and downstream reduction in cross-section area due to the coupled effects of low precipitation, strong evapo-transpiration and infiltration (Donselaar et al, 2013;Li et al, 2014a). Previous studies in this river terminus system have revealed prominent splay morphodynamics and sediment dispersal patterns (Li et al, 2014a(Li et al, , 2019(Li et al, , 2020Li and Bristow, 2015;van Toorenenburg et al, 2018). Lowfrequency but high-magnitude floods have impacted considerably on the geomorphology and sedimentology of the river terminus, in particular in the distal part and floodplain of the river terminus due to significant overbank flooding (Li et al, 2018(Li et al, , 2019.…”
Section: Study Areamentioning
confidence: 99%
“…The Río Colorado is characterised by seasonal activation and downstream reduction in cross-section area due to the coupled effects of low precipitation, strong evapo-transpiration and infiltration (Donselaar et al, 2013;Li et al, 2014a). Previous studies in this river terminus system have revealed prominent splay morphodynamics and sediment dispersal patterns (Li et al, 2014a(Li et al, , 2019(Li et al, , 2020Li and Bristow, 2015;van Toorenenburg et al, 2018). Lowfrequency but high-magnitude floods have impacted considerably on the geomorphology and sedimentology of the river terminus, in particular in the distal part and floodplain of the river terminus due to significant overbank flooding (Li et al, 2018(Li et al, , 2019.…”
Section: Study Areamentioning
confidence: 99%
“…1B-C). Previous studies have integrated remote sensing imagery and field observations in investigations of the channel-floodplain morphodynamics of the middle reaches and the fan-shaped lower reaches approaching the terminus (Donselaar et al, 2013;Li et al, 2014aLi et al, , b, 2015Li et al, , 2018Li et al, , 2019Li et al, , 2020aLi and Bristow, 2015;van Toorenenburg et al, 2018). These studies have shown that the lower reaches of the main (trunk) channel are characterised by a prominent downstream decrease in cross-sectional area (Fig.…”
Section: Study Areamentioning
confidence: 99%
“…Sparsely or non-vegetated dryland river systems are receiving increasing research attention since they provide excellent modern analogues for the study of ancient (especially prevegetation) rock records and extraterrestrial surface environments (e.g. Grotzinger et al, 2015;Dietrich et al, 2017;Li et al, 2014aLi et al, , 2020aJacobsen and Burr, 2016;Ielpi, 2018;Ielpi and Lapôtre, 2019), and also may have significance for the management of ecosystem services and flood hazards in otherwise moisture-stressed settings (Tooth, 2013;Li et al, 2018). Many low-gradient dryland rivers are terminal systems that are characterised by significant downstream decreases in cross-sectional areas and sediment transport capacity, with defined channels commonly ending on channelless plains (floodouts), in wetlands, or at playa margins (Tooth, 1999a;Tooth and McCarthy, 2007;Ralph and Hesse, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bend development and sinuosity growth are limited by the occurrence of cutoffs (Van Dijk, 2013). Previous studies have demonstrated that neck cutoffs heavily influence the development of meandering rivers in terms of planform shape, hydraulics and sedimentology, both in the short and long term (Camporeale et al, 2008; Li et al, 2020; Schwenk & Foufoula‐Georgiou, 2016).…”
Section: Introductionmentioning
confidence: 99%